Kebijakan Politik Pemerintahan Shah Jahan di Kesultanan Mughal - M. Nasihudin Ali (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The purpose of this study is to reveal and explain the reign of Shah Jahan in the Mughal Sultanate. The purpose of the study was also to determine the impact of Shah Jahan's political policies on the Mughal people. The method used in this research is the historical method. Its purpose is to reveal events that occurred during the time of Shah Jahan. This method is considered appropriate because in historical research there are stages of research, including heuristics, verification, interpretation, and historiography. The results obtained in this study are in its political policy which focuses on territorial expansion by dealing with rebellions carried out by political opponents and expelling the Portuguese from the Indian Subcontinent. So that it has a positive impact on the people, especially in the agricultural and trade (export-import) sectors.